Which way to bishopric? : origin and careers of polish bishops in the 13th century - Maciejewski, Jacek (2012)
The paper on the Polish episcopacy of the 13th century aims at giving a brief characterization of the career pattern, which readily lead to the office of ordinary bishop in the ecclesiastical province of Gniezno, between 1180 and 1320. Focusing on the specific social, territorial and institutional factors supporting Episcopal promotion, it also considers the issue of the importance of secular authority influence.